Synchronization Stability Enhancement of Grid-Following Converter under Inductive Power Grid - Hu, Bin; Zhao, Chen; Sahoo, Subham; Wu, Chao; Chen, Liang; Nian, Heng; Blaabjerg, Frede (IEEE transactions on energy conversion, 2023)
The loss of synchronization (LOS) is a main issue for dynamic behavior of grid-following converter (GFC) under inductive power grid. This letter reveals the underlying mechanism of insufficient damping or even negative damping during grid disturbance, and analyzes how the initial speed of angle-difference between PLL output and grid voltage affects the synchronization stability. Then a synchronization stability enhancement scheme to add a positive damping and a reverse angular frequency during transient process is proposed in this letter.